2009
DOI: 10.1063/1.3231789
|View full text |Cite
|
Sign up to set email alerts
|

On quantum integrability of the Landau–Lifshitz model

Abstract: Positive quantization in the presence of a variable magnetic field J. Math. Phys. 52, 112101 (2011) All the groups of signal analysis from the (1+1)-affine Galilei group J. Math. Phys. 52, 103504 (2011) We investigate the quantum integrability of the Landau-Lifshitz ͑LL͒ model and solve the long-standing problem of finding the local quantum Hamiltonian for the arbitrary n-particle sector. The particular difficulty of the LL model quantization, which arises due to the ill-defined operator product, is dea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(68 citation statements)
references
References 46 publications
0
60
0
8
Order By: Relevance
“…Even though the quantum inverse scattering method is a relatively straightforward procedure, in the AAF model the main difficulty lies in the type of the interaction Hamiltonian, namely, in the singular behavior of the quantum mechanical Hamiltonian and all other conserved charges. Let us note, that in the Landau-Lifshitz model one encounters exactly the same type of singularity, and the development of the quantum inverse scattering method required considerable effort and careful analysis of operator products and their regularization, as well as the construction of the correct Hilbert space [16][17][18]32]. It has also been shown that the self-adjointness of the operators is essentially equivalent to the S-matrix factorization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though the quantum inverse scattering method is a relatively straightforward procedure, in the AAF model the main difficulty lies in the type of the interaction Hamiltonian, namely, in the singular behavior of the quantum mechanical Hamiltonian and all other conserved charges. Let us note, that in the Landau-Lifshitz model one encounters exactly the same type of singularity, and the development of the quantum inverse scattering method required considerable effort and careful analysis of operator products and their regularization, as well as the construction of the correct Hilbert space [16][17][18]32]. It has also been shown that the self-adjointness of the operators is essentially equivalent to the S-matrix factorization.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the n-loop scattering amplitude corresponds to the product of n of these modified vertices: 15) where in the last step, we took the outcoming pseudo-particles k 1 and k 2 on-shell. We are now in the position to obtain the full scattering amplitude: 16) from which, by comparison with (4.1), we read off the S-matrix for the scattering of twoparticle,…”
Section: Scattering Of the Pseudo-particles In The Aaf Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The next is to consider larger subsectors, or directly the full sector (For a supersymmetric generalization of the undeformed case, see [76,77]). It would also be nice to consider the LLSMs obtained here at the quantum level, for example, by following [78][79][80][81].…”
Section: Jhep08(2014)110 5 Conclusion and Discussionmentioning
confidence: 99%